Immunosuppression and lymphomagenesis (Hematology Meeting Reports, 2009)
Individuals who are immunosuppressed are at an increased risk for developing aggressive, primarily B cell, lymphoproliferative disorders/lymphomas (LPDs). There are four clinical settings recognized by the WHO classification which are associated with development of LPDs: (1) primary immune disorders, (2) HIV infection, (3) iatrogenic immunosuppression following solid organ or allogenic bone marrow transplantation and (4) methotrexate therapy, usually for an autoimmune disorder. The diagnosis of LPDs is often problematic and the prognosis of the patients difficult to predict.